PERBANDINGAN PEMBELAJARAN DENGAN MENGGUNAKAN PBL (PROBLEM BASED LEARNING) DAN PJBL (PROJECT BASED LEARNING) TERHADAP HASIL BELAJAR SISWA PADA MATERI TRIGONOMETRI - Ika Nopiani; Denok Julianingsih (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2023)
The purpose of this study was to find out (1) the effect of problem based learning on student learning outcomes in trigonometry material (2) the effect of project based learning learning on student learning outcomes in trigonometry material (3) the effect of problem based learning and project based learning on results student learning on trigonometry material. This study uses a semi-experimental method. The population in this study were all students of class X-IPA SMA Wachid Hasyim 5 Surabaya. The sample in this study used 2 classes, namely from X-IPA1 and X-IPA2. Class X-IPA1 when learning uses problem based learning while class X-IPA2 uses project based learning. The sampling technique in this study used purposive sampling. The research design used was a non-equivalent control group design and the data analysis technique used was the paired sample t-test and the independent sample t-test. Based on the results of the research data obtained, namely: (1) there is a significant effect on the use of problem based learning on student learning outcomes in trigonometry material (2) there is a significant effect in the use of project based learning on student learning outcomes in trigonometry material (3) no there is a significant influence between problem based learning and project based learning on student learning outcomes in trignometry material.